2009
DOI: 10.1002/adma.200802932
|View full text |Cite
|
Sign up to set email alerts
|

RGB Emission through Controlled Donor Self‐Assembly and Modulation of Excitation Energy Transfer: A Novel Strategy to White‐Light‐Emitting Organogels

Abstract: White-light-emitting organic materials have attracted much attention because of their potential applications in display and lighting devices.[1] An ideal white-light-emitting system needs to emit the three primary RGB (red, green, and blue) colors in required intensities that cover the visible wavelength range from 400 to 700 nm. One of the most exploited strategies for this purpose is the use of physically blended multicomponent systems that simultaneously emit at the RGB wavelength region. In many cases, par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
155
0
2

Year Published

2010
2010
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 270 publications
(161 citation statements)
references
References 63 publications
(6 reference statements)
3
155
0
2
Order By: Relevance
“…[17] Morphology investigation by SEM (Figure 3) showed that the organogels possess a 3D network constructed from entangled bundles of fibrous aggregates. It is well known that an increase in the rigidity of a molecule can decrease molecular vibrations, probably suppress the internal conversion of an excited molecule, thus making the organogels highly emissive upon photoexcitation.…”
Section: Figurementioning
confidence: 99%
“…[17] Morphology investigation by SEM (Figure 3) showed that the organogels possess a 3D network constructed from entangled bundles of fibrous aggregates. It is well known that an increase in the rigidity of a molecule can decrease molecular vibrations, probably suppress the internal conversion of an excited molecule, thus making the organogels highly emissive upon photoexcitation.…”
Section: Figurementioning
confidence: 99%
“…Hence, FRET studies have been conducted in micelles [12], reverse micelles [13,14], vesicles [15], liposomes [16], ionic liquids [17,18], supramolecular assemblies [19], DNA [20], quantum dots and cyclodextrins [21], etc. Recently, there has been a spurt in energy transfer studies aimed for the development of novel white light emitting organogels like [22][23][24][25][26][27].…”
Section: = +mentioning
confidence: 99%
“…At a specific composition and temperature, partial energy transfer from the gel to the polymer resulted in white photoluminescence. [64,65] Meijer et al have functionalized three different p-conjugated oligomers 51, 52, and 53 with self-complementary quadruple hydrogen bonding ureidopyrimidinone (UPy) units at both ends ( Figure 17). The molecules self-assemble in solution and in the bulk, forming supramolecular polymers.…”
mentioning
confidence: 99%